Impoliteness Strategies of Dark Humor on Trevor Noah’s Show “Son of Patricia" - Annisa Nurul Shabrina; Hendi Pratama (English Education Journal, 2023)
This study aimed to explore the phenomenon of how something vulgar or sensitive becomes a joke to execute many meanings, which is interesting to study. It was specifically focused on dark humor presented in stand-up comedy performances as one of the famous media for presenting humor. The researcher investigated the impoliteness strategies and their contribution to express dark humor. This study used phenomenological qualitative with a pragmatic approach. It analyzed dark humor found in Trevor Noah’s stand-up comedy performance entitled “Son of Patricia” through the impoliteness strategy by Culpeper (1996). The result showed that there was 51 dark humor found in Noah’s performance. It enclosed several topics, which were his personal experiences. The most impoliteness strategies used were sarcasm or mock. It was used in all the performance topics to cover up his attacks on others’ faces by making jokes. However, withhold politeness was not found in the performance, as there was no dark humor expressed by failing to use politeness. There were some cases where two impoliteness strategies used together in a joke. The researcher hopes this study will broaden the scope of this study to encompass additional variables, populations, or timeframes. Such an expansion could provide a more comprehensive understanding of impoliteness strategies used in expressing dark humor enclosed behind the dark humor and its impact on various contexts.